2003
DOI: 10.1046/j.1365-2656.2003.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Is clutch size limited by incubation ability in northern lapwings?

Abstract: Summary1. The incubation-limitation hypothesis states that clutch size in shorebirds is constrained by the ability to incubate more than four eggs successfully. In order to test predictions from this hypothesis, clutches of northern lapwings ( Vanellus vanellus ) were here experimentally increased and reduced by one egg at the onset of incubation. Parental behaviour, incubation time, hatching synchrony, egg viability, hatching success and body condition of hatchlings was compared with unmanipulated clutches. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 48 publications
4
34
0
Order By: Relevance
“…Brooding conditions affect avian embryo growth, survival, hatchling weight, and subsequent offspring behavior and fecundity [1] [2] [3] [4]. The type of parental care of eggs, and the subsequent degree of parental influence on pre-hatch conditions, varies greatly among species [5].…”
Section: Introductionmentioning
confidence: 99%
“…Brooding conditions affect avian embryo growth, survival, hatchling weight, and subsequent offspring behavior and fecundity [1] [2] [3] [4]. The type of parental care of eggs, and the subsequent degree of parental influence on pre-hatch conditions, varies greatly among species [5].…”
Section: Introductionmentioning
confidence: 99%
“…We predicted that nestlings heated as embryos during incubation would have higher body condition (i.e. residual mass) than control nestlings due to greater retention of energy reserves, as previous work has suggested that suboptimal developmental conditions lead to reduced body condition (Larsen et al 2003), though increased temperatures can lead to increased water loss and lower mass at hatching (Reid et al 2000a). …”
Section: Introductionmentioning
confidence: 99%
“…However, reduced incubation ability may also negatively influence the performance of bird embryos in more subtle ways. In northern lapwings (Vanellus vanellus), newly hatched chicks from experimentally enlarged clutches were in poorer body condition than controls, perhaps increasing their risk of mortality (Larsen et al 2003). Further, prenatal developmental conditions can have longterm effects on zebra finch (Taeniopygia guttata) reproductive performance later in life, without producing a clear effect on growth and development (Gorman & Nager 2004).…”
Section: Discussionmentioning
confidence: 99%